Dry mortar composition
By using high reactive biomass ash and low cement content mineral adhesive, a dry mortar composition was prepared for mixing with water to form a tile adhesive, which solved the problem of insufficient performance and CO2 footprint of the tile adhesive in the prior art, and achieved a high-performance, low-carbon tile adhesion effect.
Patent Information
- Application Number
- CN202380041587.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-20
- Filing Date
- 2023-05-16
- Publication Date
- 2025-03-18
AI Technical Summary
Existing ceramic tile adhesives have shortcomings in performance and CO2 footprint, which are difficult to meet the requirements of high tensile bonding strength, long opening time and low carbon emissions.
A dry mortar composition containing 40-90% aggregate and 10-60% mineral binder is used, which contains at least 70% biomass ash and 0-6% cement, and is used for tile adhesion by mixing with water.
Achieve high tensile bond strength and long opening time that meets EN 12004-1 standards, while significantly reducing CO2 footprint, providing a low-carbon and environmentally friendly tile adhesive solution.
Smart Images

Figure BDA0005142836420000101
Abstract
Description
Technical Field
[0001] The invention relates to a dry mortar composition. Background Art
[0002] A dry mortar composition is a powdered mixture containing a hydraulic binder and aggregates. After mixing with water, it forms a paste called wet mortar, which can be applied to various substrates before setting and hardening to finally form hardened mortar. Mortar can be used, for example, as a render, plaster, flooring compound, masonry mortar, tile adhesive, grout, etc., or to make building elements by additive manufacturing. Summary of the invention
[0003] The object of the present invention is in particular to provide a mortar which can be used as tile adhesive.
[0004] Tile adhesives must meet many requirements, both in terms of ease of use when laying the tiles and in terms of the performance of the hardened mortar after laying. For example, the EN 12004-1 standard requires a tensile bond strength of at least 0.5 N / mm 2 (C1 grade adhesive), or even at least 1 N / mm 2 (C2 adhesive), even after immersion in water, heating or freeze-thaw. For adhesives with extended open time (designated "E"), the open time (between substrate bonding and tile laying while maintaining at least 0.5 N / mm 2 The maximum time for adhesion to be maintained) must be at least 20 minutes, preferably at least 30 minutes. The lateral deformation according to EN 12004 is preferably at least 2.5 mm (S1 deformation capacity) or at least 5 mm (S2 deformation capacity). Slip resistance is also an additional property; according to EN 12004, when the adhesive exhibits a slip resistance of 0.5 mm or less, it is marked with "T". Setting and curing times, workability, consistency of the wet mortar and the effort required for application are also parameters to be taken into account.
[0005] The objectives to be achieved also involved the CO 2 The hydraulic binder used in mortars for tile adhesives is typically cement, especially Portland cement, the production of which requires a lot of energy and releases large amounts of CO into the atmosphere. 2 . Therefore, it is necessary to provide a much lower CO 2 A mortar composition which has a small footprint and at the same time meets the requirements for tile adhesives.
[0006] These objects are achieved by a dry mortar composition comprising 40-90 wt.-% aggregate and 10-60 wt.-% mineral binder, the mineral binder comprising at least 70 wt.-% biomass ash and 0-6 wt.-% cement. The amount of biomass ash and cement in the mineral binder is calculated relative to the (total) amount of the mineral binder. The amount of aggregate and mineral binder in the dry mortar composition is calculated relative to the (total) amount of the dry mortar composition. As explained in further detail in this specification, the mineral binder may in particular comprise, in addition to the biomass ash, an activator, a retarder and / or an accelerator.
[0007] Another object of the present invention is a tile adhesive prepared by mixing such a dry mortar composition with water to form a paste.
[0008] Another object of the invention is the use of the dry mortar composition as tile adhesive.The term "tile adhesive" includes the dry mortar composition itself and the paste obtained by mixing the dry mortar composition with water (also called wet mortar).
[0009] Yet another object of the present invention is a method for attaching tiles to a substrate, comprising applying the above-mentioned tile adhesive to said substrate and then applying said tiles to said substrate. Such a method then comprises mixing a dry mortar composition with water to form a paste, applying said paste to a substrate and then applying the tiles to said substrate.
[0010] The inventors have surprisingly shown that tile adhesives meeting the above requirements can be obtained by using very large amounts of biomass ash and little or even no cement, in particular no or little Portland cement. 2 The footprint is thus significantly reduced.As described in more detail in this specification, the inventors have shown, inter alia, that biomass ash may in certain circumstances be more reactive than cement itself. DETAILED DESCRIPTION
[0011] Mineral Binders
[0012] Biomass ash is ash formed during the combustion of biomass, used for example to generate electricity, steam and / or heat. The biomass may for example come from agricultural products, from forest products, from household and municipal waste, from the paper or pulp industry and / or from energy crops.
[0013] Preferably, the biomass ash comprises or even consists of ash obtained from the combustion of waste (or residues or by-products) from the paper and pulp industry. These biomass ashes show high or very high reactivity. For example, such wastes are produced in the process of producing paper or paperboard from recycled paper or paperboard. These wastes can be recovered, for example, in a pulping step, in which water and chemicals such as hydrogen peroxide, sodium hydroxide and sodium silicate are added to the shredded paper to separate the cellulose fibers, and / or in a screening step.
[0014] In other embodiments, biomass ash comprises wood and the ash obtained from the burning of the residue of the pulp and paper industry or even consists of wood and the ash obtained from the burning of the residue of the pulp and paper industry. In other embodiments, biomass ash comprises wood ash or even consists of wood ash. Wood ash is produced during the burning of wood and wood products. Wood ash is obtained especially from forestry residues, waste materials (bark, sawdust ...), wood, wood residues or the burning of the residue from pulp or wood industry. Biomass can be produced, for example, during the logging activities for pulp or other wood-related industries and for the forest clearing for wildfire prevention. For example, biomass ash can comprise the fly ash obtained from the burning of wood, bark, forestry residues and / or wood residues or even consists of the fly ash obtained from the burning of wood, bark, forestry residues and / or wood residues. Timber is for example selected from pine and eucalyptus. Timber also may come from demolition engineering or household wood waste.
[0015] Whatever the origin of the biomass, the combustion is preferably carried out by fluidized bed combustion, in particular by bubbling fluidized bed combustion. Other combustion methods are fixed bed combustion or circulating fluidized bed combustion.
[0016] Regardless of the combustion method, the biomass ash used in the present invention is preferably recovered from the flue gases (e.g. by filtration), in contrast to bottom ash, which is recovered from the bottom of the boiler. Bottom ash does often contain undesirable substances, such as heavy metals.
[0017] The inventors have recognized that biomass ashes may have very different reactivity, depending on their chemical and mineralogical composition, which depends in particular on the type of biomass and the combustion technology. For example, high temperatures (at least 700 or 800° C.) make it possible to obtain interesting mineral phases, especially when the residence time of the biomass in the boiler is long. Some biomass ashes show very high reactivity (such as those obtained from the combustion of waste from the paper and pulp industry), which makes it possible to reduce the amount of cement to very low values, or even not to use cement at all. Unexpectedly, some biomass ashes show even higher reactivity than Portland cement.
[0018] The biomass ash preferably comprises, or even consists of, biomass ash having an average chemical composition comprising 5 to 35 wt. %, in particular 10 to 30 wt. %, of SiO 2 , 3-20 wt. %, especially 5-15 wt. % Al 2 O 3 , 0-5 wt %, especially 0.5-3 wt % Fe 2 O 3 and 30-70 wt. %, in particular 40-60 wt. % CaO. Such biomass ash is very reactive and is referred to herein as "highly reactive biomass ash". The biomass ash of the dry mortar composition preferably comprises at least 60 wt. %, in particular at least 70 wt. %, even at least 80 wt. % or at least 90 wt. %, or 100 wt. % of such highly reactive biomass ash, relative to the total weight of the biomass ash. Examples of these highly reactive biomass ashes are those obtained from the combustion of waste (or residues or by-products) of the paper and pulp industry, in particular when they are burned at high temperatures (above 700 or 800° C.).
[0019] Other less reactive biomass ashes have an average chemical composition of 40-55 wt% SiO 2 , 5-12 wt% Al 2 O 3 , 1-7 wt% Fe 2 O 3 , 6-23 wt% CaO and 1-7 wt% K 2 O. In particular, such a composition contains 45-52 wt. % SiO 2 , 8-10 wt% Al 2 O 3 , 2-5 wt% Fe 2 O 3 , 8-20 wt% CaO and 2-5 wt% K 2 O. In the present invention, such biomass ashes are referred to as "medium-reactive biomass ashes". The amount of medium-reactive biomass ashes is preferably less than 40% by weight, in particular less than 30% by weight or less than 20% by weight, or even less than 10% by weight or 0% relative to the total weight of biomass ashes. Examples of these medium-reactive biomass ashes are certain wood ashes.
[0020] The loss on ignition of the biomass ash is preferably less than 10% by weight, in particular less than 5% by weight, or even less than 1% by weight.
[0021] The biomass ash may be a mixture of different biomass ashes. In particular, the biomass ash may be a mixture of high-reactivity and medium-reactivity biomass ashes as defined above, for example to adjust the setting and hardening properties of the mortar. Preferably, the weight ratio between the high-reactivity and medium-reactivity biomass ashes is at least 60:40, in particular at least 70:30, even at least 80:20 or at least 90:10. As mentioned above, the biomass ash may consist of high-reactivity biomass ashes.
[0022] Relative to the total weight of biomass ash, biomass ash preferably comprises at least 10 wt% of hydraulic phase, more preferably at least 15 wt%, or even at least 20 wt% of hydraulic phase. This amount is more preferably 25 wt% or more, or even 30 wt% or more. This amount is advantageously below 60 wt%, even below 50 wt%. The hydraulic phase is preferably selected from calcium silicate, calcium aluminate, free lime (CaO) and mixtures thereof. Calcium silicate and calcium aluminate preferably comprise one or more of the following phases: C2S, C3S, C3A, C4AF, C2A2S, CA, C12A7 and CA2. Relative to the total weight of biomass ash, biomass ash preferably comprises at least 10 wt% of C2S phase, at least 5 wt% of C2A2S phase and at least 1 wt% of C3A phase. The amount of C3S phase is preferably 1 wt% or less, or even 0%, because it inhibits the formation of aluminate phase during hydration. The amount of free lime in the biomass ash is preferably at least 5 wt%, even at least 10 wt%, such as 5-18 wt%.
[0023] Biomass ash may also contain an amorphous phase, in particular CaO, Al 2 O 3 and SiO 2 , in an amount such that these elements can be dissolved. The amount of amorphous phase is, for example, 10-25% by weight.
[0024] Biomass ash may contain free (metallic) aluminum. However, the amount of this component is preferably 3 wt% or less relative to the total weight of biomass ash, because it may cause the mortar to expand during hardening, reducing the bonding value of the mortar, especially after immersion in water. In some embodiments, the amount of free aluminum is 1 wt% or less, or even 0.
[0025] The biomass ash may contain additional reactive phases such as carbonates (especially calcite), sulfates (especially calcium sulfate, such as anhydrite) or aluminosilicates (such as microcline). The amount of calcite is preferably 10-40% by weight relative to the total weight of the biomass ash.
[0026] All of the mineralogical characteristics detailed in the previous paragraphs are typically achieved with highly reactive biomass ashes.
[0027] In terms of particle size, the D50 (based on volume distribution) of biomass ash is preferably 8-50 μm, in particular 10-30 μm, for example about 15 μm. The maximum size (Dmax) is preferably 200 μm or less. These sizes are usually measured by laser granulometry.
[0028] The (total) amount of biomass ash in the mineral binder is preferably 70-95% by weight, even 75-90% by weight or 80-95% by weight (relative to the weight of the mineral binder). In some embodiments, it can be 100% by weight. The (total) amount of biomass ash in the dry mortar composition is preferably 8-60% by weight, in particular 10-50% by weight, even 20-40% by weight (in particular in the case of tile adhesives), relative to the weight of the dry mortar composition.
[0029] Preferably, the mineral binder comprises, in addition to the biomass ash, an activator (e.g. lime, slag, a source of calcium sulfate and / or optional cement) and a retarder and / or accelerator, i.e. a compound that influences, acts on or participates in the hydration reaction of the biomass ash. These compounds are therefore part of the mineral binder and their amount should be taken into account when calculating the weight of the mineral binder. On the other hand, the other components of the dry mortar, mainly aggregates and optional additives, which do not influence the hydration of the biomass ash and will be described in more detail below, are not part of the mineral binder. The use of the plural in "activators", "retarders" or "accelerators" does not mean that a plurality of activators, retarders or accelerators are present at the same time.
[0030] The mineral binder may further comprise an activator, preferably selected from cement, lime, a source of calcium sulfate, slag, metakaolin, silica fume, pozzolan, fly ash from coal combustion or oil shale combustion and mixtures thereof. In the following, all amounts are given relative to the total amount of mineral binder.
[0031] Due to the high CO 2 Footprint, relative to the total amount of mineral binder, the amount of cement in the mineral binder is preferably 0-5% by weight, even 0-4% by weight, more preferably 0-3% by weight or 0-2% by weight. The amount of cement can be 0-1% by weight, or can be 0 (i.e. the mineral binder, and therefore the dry mortar composition, does not contain cement).
[0032] When present, cement is particularly selected from Portland cement, calcium aluminate cement, calcium sulphoaluminate cement and mixtures thereof.
[0033] Cement may consist of one type of cement. Alternatively, cement may be a mixture of multiple cements. In the latter case, the term "cement" includes all cements contained in the composition, and the amount of cement (also referred to as the "total amount of cement") is the sum of the respective amounts of each specific cement contained in the composition, i.e. the total amount of all cements contained in the composition.
[0034] When present, the cement most preferably comprises CEM I cement according to EN 197-1 standard, also known as ordinary Portland cement. The cement preferably consists of (or in other words is) CEM I cement according to EN 197-1 standard. Particularly preferred are CEM I 42.5 or CEM I 52.5.
[0035] The weight ratio of biomass ash to cement is preferably 90:10 to 100:0. According to a preferred embodiment, the weight ratio is in particular 92:8 or more, or even 95:5 or more. According to another preferred embodiment, the weight ratio is 98:2 or more, or even 99:1 or more. When the mineral binder does not contain cement, it can be 100:0. The weight ratio of biomass ash to cement is calculated by dividing the total amount of biomass ash by weight by the total amount of cement by weight.
[0036] Calcium sulfate has been shown to adjust the reactivity of biomass ash. The total amount of calcium sulfate source in the mineral binder is preferably 2-15% by weight, in particular 5-10% by weight, relative to the weight of the mineral binder. The calcium sulfate source is preferably selected from gypsum, anhydrite, hemihydrate and mixtures thereof. A mixture of anhydrite and hemihydrate is particularly preferred.
[0037] The mineral binder advantageously comprises lime, in particular in an amount of 0.1-0.5% by weight relative to the total weight of the mineral binder.
[0038] The mineral binder may also contain sodium sulfate, in particular in an amount of 0.1-3 wt. %, preferably 0.5-2 wt. %, relative to the weight of the mineral binder. Sodium sulfate can activate the biomass ash and support the formation of ettringite.
[0039] The total amount of slag is preferably 0-15% by weight, even 0.5-15% by weight, and the weight is particularly 1-10% by weight (relative to the weight of the mineral binder). The slag is preferably selected from blast furnace slag, basic oxygen slag, electric arc furnace slag, ladle slag, high aluminum slag and mixtures thereof. High aluminum slag is preferably recovered by completely melting a catalyst (especially a catalyst based on molybdenum and / or cobalt) for desulfurization of petroleum products. Other high aluminum slags from pyrometallurgy can also be used. The presence of slag can increase adhesion after immersion in water and under freeze-thaw hardening conditions. Relative to the weight of the mineral binder, the total amount of silica fume is preferably 0-5% by weight. The mineral binder (and therefore, mortar) may not contain silica fume.
[0040] The mineral binder preferably contains an inorganic oxide salt to reduce the expansion of the binder during hardening. This is particularly interesting when the biomass ash contains free aluminum. The inorganic oxide salt is preferably selected from nitrates, carbonates and permanganates. The counterion is preferably an alkali metal. Lithium is particularly preferred because it also improves the hardening of the binder. Examples of inorganic oxide salts are lithium nitrate, lithium carbonate, potassium nitrate and potassium permanganate. Lithium nitrate is particularly preferred. The amount of inorganic oxide salt (especially lithium nitrate) in the mineral binder is preferably 0.1-2.0% by weight, especially 0.5-1.0% by weight, relative to the weight of the mineral binder.
[0041] The mineral binder preferably further comprises at least one accelerator and / or at least one retarder, so as to adjust the setting and / or hardening time, and reduce the expansion of the mineral binder. Preferably, in particular for highly reactive biomass ash, the mineral binder comprises at least one retarder. Retarder can delay the formation of Aft, AFm and CSH phases, thereby increasing the open time. In addition, retarder helps to increase the Aft / AFm ratio, which leads to better dimensional stability. Preferred retarders are carboxylic acids or their salts, such as tartaric acid or citric acid or their salts, and mixtures thereof. Unexpectedly, carboxylic acids and their salts have been shown to reduce the expansion of adhesives during hardening. The combination of tartaric acid and citric acid is particularly preferred. Relative to the weight of the mineral binder, the total amount of retarder is preferably 0.01 to 1.0 weight %, particularly 0.05 to 0.5 weight %.
[0042] The setting accelerator is, for example, an alkali metal salt such as lithium (or potassium) sulfate or carbonate, or an organic salt such as calcium formate. When present, the total amount of setting accelerator is preferably 0.1-3.0 wt%, especially 0.2-2.0 wt%, relative to the weight of the mineral binder.
[0043] aggregate
[0044] The aggregate is preferably selected from siliceous, calcareous, dolomitic aggregates and mixtures thereof. Examples are ground limestone or dolomite and silica sand. The aggregate preferably comprises sand (size 0-5 mm) and possibly fillers (size 0-0.1 mm). The aggregate preferably comprises silica sand (or even consists of silica sand). A mixture of silica sand and limestone is also possible. Alternatively or cumulatively, the aggregate may comprise lightweight aggregate, i.e. an apparent density of at most 600 kg / m 3 Aggregates such as hydrophobic expanded perlite, thermosetting polymer powders (such as micronized rubber powder), hollow silicate particles (such as expanded glass beads and / or hollow microspheres) and mixtures thereof. When the mortar is used as a tile adhesive, the maximum size of the aggregate is preferably 2 mm, or even 1 mm.
[0045] The total amount of aggregate is preferably in the range of 50-85 wt%, in particular 55-80 wt%, or even 60-75 wt%.
[0046] The average diameter (D50) of the aggregates based on volume distribution is preferably 0.20 mm or less, in particular 0.15 mm or less, even 0.10 mm or less.
[0047] additive
[0048] The dry mortar composition further preferably comprises one or more additives selected from the group consisting of redispersible polymer powders, pigments, defoamers, stabilizers, thickeners, water retaining agents, shrinkage reducing agents, hydrophobic agents, plasticizers and superplasticizers. The total amount of these additives is preferably 0.1-8.0% by weight, in particular 0.5-3.0% by weight, relative to the weight of the dry mortar composition.
[0049] More preferably, the dry mortar composition comprises a redispersible polymer powder and a water retaining agent.
[0050] Thickeners and water retaining agents are, for example, cellulose ethers and / or starch ethers. Their total amount is preferably 0.1-1.0 wt %, in particular 0.2-0.6 wt %. These additives can improve the workability of the paste.
[0051] The redispersible polymer powder preferably comprises at least one polymer based on one or more monomers selected from the group consisting of vinyl esters (especially vinyl esters of unbranched or branched alkyl carboxylic acids having 1 to 15 carbon atoms), methacrylates and acrylates (especially (meth)acrylates of alcohols having 1 to 10 carbon atoms), methacrylic acid, acrylic acid, vinyl aromatics, olefins (such as ethylene or propylene), dienes and vinyl halides. Particularly preferred polymers are copolymers of at least two of the above monomers, especially vinyl acetate-ethylene copolymers, vinyl ester-ethylene-vinyl chloride copolymers, vinyl acetate copolymers, vinyl acetate-acrylate copolymers, copolymers of methyl methacrylate with n-butyl acrylate and / or 2-ethylhexyl acrylate, copolymers of methyl methacrylate with 1,3-butadiene, vinyl chloride-ethylene copolymers, vinyl chloride-acrylate copolymers, styrene-butadiene copolymers, styrene-acrylate copolymers, vinyl acetate-(meth)acrylic acid-ethylene terpolymers. The amount of redispersible polymer powder is preferably 0.2-8.0 wt %, in particular 0.5-6.0 wt %, even 1.0-5.0 wt %.The glass transition temperature (Tg) of the polymer is preferably 5-20°C.
[0052] The ratio of water to dry mortar composition ("water-cement ratio") is preferably 0.15-0.40 by weight to obtain a suitable paste (wet mortar) consistency. This corresponds to a water dosage of 15-40% (added to 100% dry mortar).
[0053] The paste formed by mixing the dry mortar composition with water is applied to the substrate by conventional techniques.
[0054] The substrate is typically a wall or partition, or a floor, such as a screed.
[0055] The tiles or slabs to be laid can be of various materials, such as ceramic, sandstone, cement, stone, marble, etc. Wet mortar (adhesive) can be applied to the substrate by means of a glue comb, hawk, float, trowel or notched trowel, or to the tiles or slabs.
[0056] According to EN 12004-1:2017, tile adhesives are preferably classified as C1, C2 or C2S.
[0057] Other applications of the dry mortar composition are also possible, such as for exterior wall renders or plasters, flooring compounds (such as screeds) or tile mortars. It can also be used in 3D-printing processes for the manufacture of building elements (such as walls).
[0058] Example
[0059] The following examples illustrate the invention in a non-limiting manner.
[0060] Dry mortar compositions used as tile adhesives have been obtained by mixing different ingredients. The following table shows the composition (amounts in wt. %, relative to the weight of the dry mortar composition) and some measured properties of examples (1-6) according to the invention.
[0061] Biomass ashes are obtained from the combustion of waste from the paper and pulp industry and were supplied by SAICA, Spain. Their chemical composition contains 10-30 wt% SiO 2 , 5-15 wt% Al 2 O 3 , 0.5-3 wt% Fe 2 O 3and 40-60% by weight of CaO. In terms of the mineral composition, the ash contains in particular 34% by weight of calcite, 8% by weight of lime, 15% by weight of larnite (C2S), 6% by weight of gehlenite (C2A2S), 2% by weight of tricalcium aluminate (C3A), 3% by weight of other hydraulic phases, 1% by weight of anhydrite, 2% by weight of free aluminum and 19% by weight of amorphous phases. Their D50 (based on volume distribution) is 14 μm and their D90 is 51 μm.
[0062] The cement designated "OPC" in the table is CEM I 42.5 Portland cement. The slag is ground granulated high-alumina slag recovered by complete melting of a catalyst based on molybdenum and / or cobalt. The calcium sulfate is a mixture of anhydrite and hemihydrate. The cellulose ether is hydroxyethyl methylcellulose with a viscosity between 20000-40000 mPas (after addition of water). The "resin" is a redispersible powder which is an EVA copolymer with a Tg of 16°C.
[0063] For each example, the table shows the results of setting time at 22° C., tensile bond strength under different conditions and after 20 minutes open time (measured according to EN 12004-2 standard), and qualitative evaluation of expansion and workability.
[0064] [Table 1]
[0065]
[0066] Examples 5 and 6 show the effect of lithium nitrate and carboxylic acid in reducing expansion during hardening.
Claims
1. A dry mortar composition comprising 40-90 wt. % of aggregate and 10-60 wt. % of mineral binder, relative to the weight of the dry mortar composition, The mineral binder comprises at least 70% by weight of biomass ash and 0-6% by weight of cement, relative to the weight of the mineral binder.
2. The dry mortar composition according to claim 1, wherein The biomass ash comprises ash obtained from the combustion of paper and pulp industry waste.
3. A dry mortar composition according to any one of the preceding claims, wherein: The biomass ash comprises biomass ash having an average chemical composition comprising 5-35 wt % SiO 2 , 3-20 wt % Al 2 O 3 , 0-5 wt % Fe 2 O 3 , and 30-70 wt % CaO.
4. A dry mortar composition according to any one of the preceding claims, wherein: The biomass ash comprises at least 10 wt. %, preferably at least 20 wt. % of a hydraulic phase, relative to the total weight of the biomass ash.
5. A dry mortar composition according to any one of the preceding claims, wherein: The hydraulic phase is selected from calcium silicate, calcium aluminate, free lime (CaO) and mixtures thereof.
6. A dry mortar composition according to any one of the preceding claims, wherein: The calcium silicates and calcium aluminates include one or more of the following phases: C2S, C3S, C3A, C4AF, C2A2S, CA, C12A7 and CA2.
7. A dry mortar composition according to any one of the preceding claims, wherein: The amount of biomass ash in the mineral binder is 70-95 wt%, in particular 75-95 wt%, relative to the weight of the mineral binder.
8. A dry mortar composition according to any one of the preceding claims, wherein: In addition to biomass ash, the mineral binder also contains an activator and a setting retarder and / or a setting accelerator.
9. A dry mortar composition according to any one of the preceding claims, wherein: The activator is selected from the group consisting of lime, calcium sulfate sources, slag, metakaolin, silica fume, pozzolan, fly ash from coal combustion or from oil shale combustion, and mixtures thereof.
10. A dry mortar composition according to any one of the preceding claims, wherein: The total amount of the slag is 0-15 wt % relative to the weight of the mineral binder.
11. A dry mortar composition according to any one of the preceding claims, wherein: The amount of cement in the mineral binder is 0-4% by weight, preferably 0-1% by weight, relative to the total weight of the mineral binder.
12. A dry mortar composition according to any one of the preceding claims, wherein: The mineral binder comprises an inorganic oxidic salt of an alkali metal, in particular selected from nitrates, carbonates and permanganates.
13. A dry mortar composition according to any one of the preceding claims, wherein: The mineral binder comprises carboxylic acids or salts thereof, in particular tartaric acid or citric acid or salts thereof, and mixtures thereof.
14. A dry mortar composition according to any one of the preceding claims, wherein: The aggregate is selected from siliceous aggregate, calcareous aggregate, dolomite aggregate and mixtures thereof.
15. The dry mortar composition according to any one of the preceding claims, comprising one or more additives selected from the group consisting of redispersible polymer powders, pigments, defoamers, stabilizers, thickeners, shrinkage reducers, hydrophobic agents, plasticizers and superplasticizers.
16. A tile adhesive prepared by mixing the dry mortar composition of any one of the preceding claims with water to form a paste.
17. A method for sticking tiles on a substrate, comprising mixing the dry mortar composition according to any one of claims 1 to 15 with water to form a paste, applying the paste to the substrate, and then applying the tiles to the substrate.
18. Use of the dry mortar composition according to any one of claims 1 to 15 as a tile adhesive.